The Application Of Formulaic Expressions In The Conversation Texts Of Senior High School English Textbooks - Sugiati, Ana; Rukmini, Dwi (Universitas Negeri Semarang, 2017)
The main objective of this study was to analyze the application of formulaic expressions in the conversation texts of senior high school English textbooks grade X, XI, and XII entitled â€œBahasa Inggrisâ€ published by the Ministry of Education and Culture. This topic was chosen because formulaic competence is a component of the communicative competence that helps the students to speak native-like. The researcher applied qualitative approach and used discourse analysis as the design of the study. The objects of the study were twenty-five conversation texts of English textbooks grade X, XI, and XII. They were analyzed based on the list of formulaic expressions proposed by Biber et al. (1999). The researcher found that the application of the formulaic expressions in the conversation texts of the English textbooks was not fully done. There were only four out of five formulaic expressions types as formulated by Biber et al. (1999). They were lexical bundles, idiomatic phrases, collocations, and inserts. They did not frequently occur in the conversation texts of the textbooks. They were only 21.9% of the total expressions. It was concluded that the expressions were not native-like, so the conversation texts of the textbooks need to be improved.